Influence of edible flowers on the physicochemical and oxidative stability of raw ground beef patties - Krishna Brunda Duggirala; Gopinath Mummaleti; Fanbin Kong; Anand Mohan (Frontiers in Food Science and Technology)
This study investigates the antioxidant and physicochemical characteristics of raw ground beef patties and raw ground beef patties treated with varying percentages of roselle (Hibiscus sabdariffa L.) and rose (Rosa canina L.) powders during 7 days of storage at 4°C. The analysis included key parameters such as antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, lipid oxidation through 2-thiobarbituric acid reactive substances (TBARS), protein oxidation markers (carbonyls, Schiff bases, and free thiols), water-holding capacity, pH, color, and texture. Both roselle and rose powders enhanced the antioxidant capacity of the patties, reducing oxidative markers (TBARS, carbonyls, Schiff bases, and free thiols) during storage. Additionally, improved water-holding capacity and reduced pH were observed across all treated patties, with minimal impact on texture. However, while roselle powder showed beneficial effects, patties treated with rose powder exhibited superior overall results. The more favorable outcomes in rose-treated patties, particularly in oxidative stability and physicochemical properties, can be attributed to the higher concentrations of bioactive compounds, such as phenolic acids and flavonoids, present in rose powder. These compounds likely contributed to enhanced free radical scavenging activity, providing stronger protection against lipid and protein oxidation. Furthermore, rose powder maintained more stable color and physicochemical properties, with patties showing acceptable color and minimal texture degradation by the 7th day of storage. These findings highlight the potential of rose powder as a highly effective natural additive for extending the shelf life and preserving the quality of ground beef patties, positioning it as a promising ingredient for future applications in the food industry.